2020
DOI: 10.1371/journal.pone.0230130
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and management of parathyroid gland disorders in Spain over 15 years: A retrospective multicentre analysis

Abstract: Parathyroid gland disorders are rare conditions with an incidence that displays great variability among populations. Its direct influence in calcium homeostasis originates variable symptoms that affect bone remodelling among other processes. This study aimed to provide data on the epidemiology and characteristics of patients admitted with these disorders in Spain between 2003 and 2017, and to analyse disease management and direct medical costs. Medical records in which a disorder of the parathyroid gland was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…The mean LOS for HypoPT-related inpatient hospitalizations in our study was between 6.5 and 7.2 days and was consistently longer across all years than those reported for non-HypoPT-related stays. Our data are consistent with findings from a retrospective study in Spain by Darba et al where patients with HypoPT-related admissions spent a mean of 7.2 days in the hospital [ 24 ]. Similarly, the Italian study by Cipriani et al reported a mean LOS of 7.4 days for HypoPT-related hospitalizations between 2006 and 2013 [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The mean LOS for HypoPT-related inpatient hospitalizations in our study was between 6.5 and 7.2 days and was consistently longer across all years than those reported for non-HypoPT-related stays. Our data are consistent with findings from a retrospective study in Spain by Darba et al where patients with HypoPT-related admissions spent a mean of 7.2 days in the hospital [ 24 ]. Similarly, the Italian study by Cipriani et al reported a mean LOS of 7.4 days for HypoPT-related hospitalizations between 2006 and 2013 [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of primary hyperparathyroidism (pHPT) is 0.1% to 0.4% in the general population [ 1 ] and its incidence is increasing, leading to an increased need for surgical management [ 2 , 3 ]. Usually, it is caused by a solitary parathyroid adenoma and surgical resection is the choice of treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to epidemiological studies, which demonstrate that the age-adjusted incidence of PHPT increases with age, the ages of our study population had clustered in the late 50 years. 10 This is due to the design of our study, which includes only patients operated for PHPT rather than being a population survey. Patient age being one of the indications for surgery and early postmenopausal women being more likely to undergo bone mineral density scanning than the elderly, resulting in increased diagnoses of asymptomatic osteoporosis, are possible reasons for the age distribution of our study population.…”
Section: Discussionmentioning
confidence: 99%